Anatomy of Trabeculae Lumbar Vertebrae On a Bats (Megachiroptera) - Hidayah, Alfi; AR, Alif Nailil Muna; Chirstanty, Agatha Yolanda; Luthfi, Muhammad Jafar (Proceeding International Conference on Science and Engineering, 2020)
Bats are the only mammals that can fly. Because of their ability to fly, making the tension received by the bat’s spine comes from the front and back.Spongy bone, also known as cancellous bone or trabecular bone, is a very porous type of bone found in animals. It is highly vascularized and contains red bone marrow. Spongy bone is usually located at the ends of the long bones (the epiphyses), with the harder compact bone surrounding it. It is also found inside the vertebrae, in the ribs, in the skull and in the bones of the joints. Spongy bone is softer and weaker than compact bone, but is also more flexible. It is characterized by a lattice-like matrix network called trabeculae (Latin for little beam) that gives it its spongy appearance. Observation of trabeculae can be done by removing the flesh, muscles, and all the tissues attached to the lumbar vertebrae bone. Then the lumbar vertebrae was sanded and to know the anatomy of the trabeculae, it was done by observing the lumbraris vertebrae using a binocular microscope and taking pictures using a camera. Then the structure is analyzed. The observations showed that the anatomical structure of the lumbar vertebrae trabeculae in bats are stressed by tension must be withstood, a ligament being as strong for its weight.